(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Echinococcosis is a parasitic disease endemic in many parts of the world. Liver is the most common affected organ followed by lungs. Primary pulmonary involvement is very rare. In this case report, we are going to present a case of primary pulmonary echinococcosis in a middle age female. She was presented with cough and haemoptysis. She was initially labeled and treated as a case of consolidation with different antibiotics in appropriate dose and duration without clinical and radiological improvement. So she was evaluated further and diagnosed as a case of primary pulmonary echinococcosis on the basis of histopathology and positive serology for Echinococcal antigen. She was advised to take oral Albendazole 400mg 12 hourly for one year with regular follow-up.